2020
DOI: 10.31940/ijaste.v4i1.1607
|View full text |Cite
|
Sign up to set email alerts
|

Okokan Tradition: Understanding Noble Value in the Frame of Symbolic Interactionalism

Abstract: Purpose: This study aims to explore the meaning of the noble value of the Okokan Art tradition in the Village of Kediri, Tabanan, Bali Province by using the symbolic interactionism point of view. Research methods: The case studies are used as a method in discussing symbolic interactions that occur in the Okokan tradition performers. Results and discussions: Based on the results of scientific studies in the field, it was found that the Okokan tradition is a form of representation of noble va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Where everything related to the Performing Arts is commodified and even the sacred is removed. So, there was a disruption of the performing arts of this okokan (Wulandari, 2020). In 2020, similar research was also found on the commodification of the okokan tradition with the result that there was a level of participation of the people of Kediri Village in the development of the Okokan tradition, including in the form of consultation levels.…”
Section: Introductionmentioning
confidence: 65%
“…Where everything related to the Performing Arts is commodified and even the sacred is removed. So, there was a disruption of the performing arts of this okokan (Wulandari, 2020). In 2020, similar research was also found on the commodification of the okokan tradition with the result that there was a level of participation of the people of Kediri Village in the development of the Okokan tradition, including in the form of consultation levels.…”
Section: Introductionmentioning
confidence: 65%
“…As a result, art has become an integral aspect of each region. Apart from its role as a native culture with noble values, art can also help the country earn foreign exchange (Wulandari, Upadani and Alfarisi 2020). Yogyakarta is home to a variety of arts, one of which is traditional village art still practiced today.…”
Section: Introductionmentioning
confidence: 99%
“…The development of this tradition year after year has increasingly changed, at this time the Okokan Tradition is no longer used as an epidemic of disease but has become an art performance staged by bringing colossal stories such as Giri Toh Langkir, Mahabarata, Nangluk Merana [5].…”
Section: Introductionmentioning
confidence: 99%